Antifibrinolytic Therapy in Neurosurgical Oncology: A Randomized, Double-Blind, Placebo-Controlled Trial on the Efficacy and Safety of Tranexamic Acid for Hypervascular Intracranial Meningiomas - Dwiandi Susilo (Sriwijaya Journal of Surgery, 2025)
Introduction: Resection of hypervascular intracranial meningiomas is frequently complicated by significant intraoperative hemorrhage, increasing patient morbidity and transfusion requirements. Tranexamic acid (TXA), an antifibrinolytic agent, has shown promise in other surgical fields, but high-level evidence in intracranial tumor surgery is lacking. This study aimed to rigorously evaluate the efficacy and safety of perioperative TXA in reducing blood loss during craniotomy for convexity and spheno-orbital meningiomas. Methods: This single-center, double-blind, randomized, placebo-controlled trial enrolled 30 adult female patients scheduled for elective resection of convexity or spheno-orbital meningiomas. Patients were randomized to receive either intravenous TXA (15 mg/kg bolus followed by a 1 mg/kg/hr infusion) or a matching saline placebo. The primary outcome was total intraoperative blood loss. Secondary outcomes included transfusion volume, perioperative changes in hematological and coagulation parameters, and the incidence of thromboembolic events within 30 days. Results: The TXA group (n=15) and the placebo group (n=15) were well-matched at baseline. Mean intraoperative blood loss was significantly lower in the TXA group compared to the placebo group (765.0 ± 94.39 mL vs. 1010.0 ± 131.20 mL; mean difference, -245 mL; 95% CI, -444.2 to -45.8; p = 0.019; Cohen's d = 2.15). The TXA group exhibited a significantly smaller postoperative drop in hemoglobin (-0.97 g/dL vs. -2.36 g/dL; p = 0.041) and significantly lower D-dimer levels at 24 hours (850 ± 210 ng/mL vs. 1620 ± 450 ng/mL; p < 0.001). There was no significant difference in PRBC transfusion volume (p = 0.410). No thromboembolic events were recorded in either group. Conclusion: In patients undergoing resection of hypervascular convexity and spheno-orbital meningiomas, perioperative TXA administration significantly reduces intraoperative blood loss and preserves postoperative hemoglobin. The agent demonstrated a favorable safety profile with no observed increase in thromboembolic risk in this cohort